Unfolding matters in public food procurement: contextualizing lessons and steps forward in school food policy reform - Lozano, Camilo; Schneider, Sergio; Swensson, Luana; Kelly, Siobhan (Raízes: Revista de Ciências Sociais e Econômicas, 2016)
This article seeks to identify the core dimensions of and the challenges to innovative school food reforms. Aiming to frame the discussion, the article examines three school feeding strategies: the World Food Programme’s Purchase for Progress (P4P) programme, the Brazilian School Feeding Program, and the European Public Food Procurement system. The first part conceptually defines what is meant by innovative forms of school food procurement, especially regarding its underlying values. It shows that school food reforms go beyond improving access to food, enhancing educational outputs and supporting economic development goals. School feeding holds a transformative potential, insofar as institutional purchases become organized and develop in line with the goals of sustainable development, well-being and social justice. In the second part, we present contemporary examples of good school feeding practices, whose elements might, or might not, be pertinent in particular cases. There are two main lessons emerging from our research. First, policy reform and governmental will are not enough, if the institutional and legal frameworks for operationalizing new school feeding programs are not adjusted to local conditions. Second, we argue that procurement policies or city food strategies can open spaces of manoeuvre within fiscal, material and governance constraints, although the role of social actors is essential and constructive for the success of nesting policy innovations